2021
DOI: 10.9734/ajpas/2021/v15i430368
|View full text |Cite
|
Sign up to set email alerts
|

Kumaraswamy-Janardan Distribution: A Generalized Janardan Distribution with Application to Real Data

Abstract: The quest to improve on flexibility of probability distributions motivated this research. Four-parameter Janardan generalized distribution known as Kumaraswamy-Janardan distribution is proposed through method of parameterization and studied. The probability density function, cumulative density function, survival rate function as well as hazard rate function of the distribution are established. Statistical properties such as moments, moment generating function as well as maximum likelihood of the model are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ranneby [15] proposed the maximum product spacing (MPS) method as an alternative to MLE for estimating the unknown parameters of continuous univariate distributions [8] and independently developed the MPS method as an approximation to the Kullback-Leibler measure of information. Cheng [16] demonstrated that this method is as efficient as MLE estimators and consistent under more general conditions, which motivated our choice.…”
Section: Maximum Product Of Spacings Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranneby [15] proposed the maximum product spacing (MPS) method as an alternative to MLE for estimating the unknown parameters of continuous univariate distributions [8] and independently developed the MPS method as an approximation to the Kullback-Leibler measure of information. Cheng [16] demonstrated that this method is as efficient as MLE estimators and consistent under more general conditions, which motivated our choice.…”
Section: Maximum Product Of Spacings Estimatorsmentioning
confidence: 99%
“…As a result, several studies have developed a more flexible distribution. See [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%